Comparison of MicroRNAs Mediated in Reactivation of the γ-Globin in β-Thalassemia Patients, Responders and Non-Responders to Hydroxyurea. (4th March 2017) - Hojjati, Mohammad T.; Azarkeivan, Azita; Pourfathollah, Ali A.; Amirizadeh, Naser
Abstract: Drug induction of Hb F seems to be an ideal therapy for patients with hemoglobin (Hb) disorders, and many efforts have been made to reveal the mechanism behind it. Thus, we examined in vivo expression of some microRNAs (miRNAs) that are thought to be involved in this process. Among β-thalassemia (β-thal) patients who were undergoing hydroxyurea (HU) therapy in the past 3 months and five healthy individuals, five responders and five non-responders, were also included in the study. Erythroid progenitors were isolated by magnetic activated cell sorting (MACS) and miRNA expression analyzed using reverse transcription-polymerase chain reaction (RT-PCR). We showed that γ-globin, miR-210 and miR-486-3p had higher levels in the responders than the non-responders group. Moreover, miR-150 and miR-320 had higher levels in the healthy group than both non-responders and responders groups, but the expression of miR-96 did not show any significant difference between the study groups. To the best of our knowledge, this is the first study proposing that 'induction of cellular hypoxic condition by Hb F inducing agents' could be the milestone of possible mechanisms that explain why responders are able to reactivate γ-globin genes and subsequently, more production of Hb F, in response to these agents in comparison to non-responders. However, further investigations need to be performed to verify this hypothesis.